Diversity and Community Structure of Dragonfly and Damselfly (Odonata) at the Selorejo Waterfall Area, Ponorogo Regency, East Java Indonesia - Susanto, Muhamad Azmi Dwi; Zulaikha, Siti (Universitas Negeri Surabaya, 2021)
Selorejo Waterfall is a natural tourism area that is quite far from downtown Ponorogo and directly adjacent to the Gunung Sigogor Nature Reserve. Hence, this area has the potential as a natural habitat for dragonfly and damselfly. The presence of dragonfly and damselfly species is determined by the type of habitat, canopy conditions, vegetation diversity, and the microclimate that exists in a location. This study aimed to determine the diversity of dragonfly and damselfly and to determine the community structure of dragonflies in Selorejo Waterfall. The sampling method was Visual Day Flying. The results of research conducted in two streams showed that there were 12 species from 6 families with a total of 230 individuals. The value of species diversity at this location is H '= 2.05. In the community structure at the Selorejo Waterfall dragonfly, there are differences in the number of species and individuals in the two streams in Selorejo Waterfall Area. The large stream, eight species from four families, 151 individuals in total. Meanwhile, in small stream, there were nine species from six families, 79 individuals in total. The differences in the number of species and individual dragonflies in the two streams at Selorejo Waterfall can be used to describe the diversity and structure of the Odonata community in the area.